Fictional Levels in the Theater Within the Cinema: Representation in the Film Caesar Must Die by the Taviani Brothers. - Linares Ávila, Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The objective of this research is to study the film César must die in relation to the construction of the fictional levels that compose it and the implications of its intermediate condition within the phenomenon called “theater within cinema”. From theoretical considerations on fiction and the notion of theatricality in cinematographic art, the film is approached on the basis of tools of film discourse analysis and semiotic analysis of the scene, with special interest in the processes of estrangement typical of Brechtian cinema.